Identification of novel adenovirus genotype 90 in children from Bangladesh. Issue 10 (24th September 2018) - Houldcroft, Charlotte J.; Beale, Mathew A.; Sayeed, Md Abu; Qadri, Firdausi; Dougan, Gordon; Mutreja, Ankur
Abstract : Novel adenovirus genotypes are associated with outbreaks of disease, such as acute gastroenteritis, renal disease, upper respiratory tract infection and keratoconjunctivitis. Here, we identify novel and variant adenovirus genotypes in children coinfected with enterotoxigenic Escherichia coli, in Bangladesh. Metagenomic sequencing of stool was performed and whole adenovirus genomes were extracted. A novel species D virus, designated genotype 90 (P33H27F67) was identified, and the partial genome of a putative recombinant species B virus was recovered. Furthermore, the enteric types HAdV-A61 and HAdV-A40 were found in stool specimens. Knowledge of the diversity of adenovirus genomes circulating worldwide, especially in low-income countries where the burden of disease is high, will be required to ensure that future vaccination strategies cover the diversity of adenovirus strains associated with disease.